2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26351
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Dimensions of Disciplinary Culture to Enhance Innovation and Retention among Engineering Students

Abstract: is an Associate Professor of Engineering Education at Virginia Tech, where she also serves as co-Director of the VT Engineering Communication Center (VTECC) and CATALYST Fellow at the Institute for Creativity, Arts, and Technology (ICAT). Her research interests include interdisciplinary collaboration, design education, communication studies, identity theory and reflective practice. Projects supported by the National Science Foundation include exploring disciplines as cultures, interdisciplinary pedagogy for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…First, there are different disciplinary perceptions and motivations regarding accepting risks. For example, disciplines like industrial and systems engineering have relatively low uncertainty avoidance [39] because of the many different career paths students can take and how flexible is the discipline in terms of the type of problems they solve. In contrast, disciplines like Civil Engineering are required to have less acceptance of uncertainty because of the type of work they do [40], [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there are different disciplinary perceptions and motivations regarding accepting risks. For example, disciplines like industrial and systems engineering have relatively low uncertainty avoidance [39] because of the many different career paths students can take and how flexible is the discipline in terms of the type of problems they solve. In contrast, disciplines like Civil Engineering are required to have less acceptance of uncertainty because of the type of work they do [40], [41].…”
Section: Discussionmentioning
confidence: 99%
“…We consider this result to be important and that has several implications for how engineering students will operate across disciplines. Research suggest that engineering students tend overall to be more individualistic [6], [39], [42]. Part of this characteristic comes from the fact that early in their academic programs, engineering student courses tend to focus on more individualistic learning (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Masculine cultures thus experience a greater gap between men's and women's roles [9], [10], [12] Despite Hofstede's theory receiving some criticism (see [14] for full details), we consider there is value in testing Hofstede's theory of dimensions of national culture in academic settings. Hofstede's model uses dimensions of culture that have been validated in a variety of contexts and scenarios [14], [15], and we have been using his theory to explore different engineering disciplines [6]- [8], [8], [14].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Second, content validity was discussed and determined by the researchers in consensus. Third, construct validity is addressed by using a survey that has been proven to be an effective tool to assess the cultural dimensions of a group [6] for review and the authors even demonstrated its validity in academic settings [15].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation